2022
DOI: 10.3390/v14051030
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations among Different Variants of G1-like Avian Influenza H9N2 Viruses and Their Pathogenicity in Chickens

Abstract: Since it was first discovered, the low pathogenic avian influenza (LPAI) H9N2 subtype has established linages infecting the poultry population globally and has become one of the most prevalent influenza subtypes in domestic poultry. Several different variants and genotypes of LPAI H9N2 viruses have been reported in Egypt, but little is known about their pathogenicity and how they have evolved. In this study, four different Egyptian LPAI H9N2 viruses were genetically and antigenically characterized and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…By sequencing 3 sample strains, we were able to select the currently circulating challenging viruses in 2022 that had a high identity percentage with vaccine strain. The phylogenetic analysis revealed that strains in our study belong to A/quail/Hong Kong/G1/97-like clustered with G1-B sub lineage EGY-2 group as previously reported ( Kandeil et al, 2014 ; Kaoud et al, 2014 ; El-Shall et al, 2019 ; Adel et al, 2022 ). They had 95.6–98.6% amino acids identity percent with previously isolated strains in Egypt from 2014 to the present due to H9N2 AI continuously evolving ( Kandeil et al, 2014 ), and they had 92.2% to 92.6% amino acids identity percent with A/chicken/Iran/av1221/1998 (Boehringer Ingelheim) vaccination used.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…By sequencing 3 sample strains, we were able to select the currently circulating challenging viruses in 2022 that had a high identity percentage with vaccine strain. The phylogenetic analysis revealed that strains in our study belong to A/quail/Hong Kong/G1/97-like clustered with G1-B sub lineage EGY-2 group as previously reported ( Kandeil et al, 2014 ; Kaoud et al, 2014 ; El-Shall et al, 2019 ; Adel et al, 2022 ). They had 95.6–98.6% amino acids identity percent with previously isolated strains in Egypt from 2014 to the present due to H9N2 AI continuously evolving ( Kandeil et al, 2014 ), and they had 92.2% to 92.6% amino acids identity percent with A/chicken/Iran/av1221/1998 (Boehringer Ingelheim) vaccination used.…”
Section: Discussionsupporting
confidence: 84%
“…Due to its great genetic evolution and the emergence of new strains resistant to existing vaccination, H9N2 virus infection is only partially protected or prevented by vaccination (Adel et al, 2022) . As a result of this, there is an ongoing requirement to make use of natural immunostimulant ( Spirulina ) as chicken feed additives to improve the efficacy of vaccines (Eladl et al, 2020) .…”
Section: Introductionmentioning
confidence: 99%
“…The phylogenetic characteristics classified the virus into three distinct lineages named after their prototype strains, i.e., the G1 linage (A/Quail/Hong Kong/G1/1997); the BJ94 lineage, also known as Y280 (A/Chicken/Beijing/1/94); and the Y439 lineage, often mentioned as the ‘Korean’ lineage [ 3 , 4 , 5 ]. Further classification of the geographically most widespread G1 lineage is not fully clarified: some authors describe four sub-lineages designated as A, B, C, and D [ 5 , 6 ], while others distinguish ‘Western’ (W) and ‘Eastern’ (E) sub-lineages [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent examination of the viruses from the affected sites indicated that they were monophyletic of the G1 lineage [ 11 , 12 ]. A recent paper found that H9N2 strains isolated from vaccinated chicken farms in Egypt belonged to the G1-B sub-lineage [ 6 ]. H9N2 LPAIV was detected in poultry in sub-Saharan Africa in 2017 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%